(Il)liberal Organisation? Internal Party Democracy on the European Radical Left - Charalambous, Giorgos (PARTECIPAZIONE E CONFLITTO, 2021)
The relationship between the European radical left and democracy has come into attention due to the electoral surges of some such parties and their participation in government. Its scrutiny, however, remains ambivalent, at a time contemporary democracies are experiencing historic disruptions affecting how people engage with parties. This study offers an organisational perspective of the European radical left in order to map out and elaborate on patterns of democratic practice in this party family, as measured against a broadly liberal benchmark. Using a modified version of the internal party democracy (IPD) index developed by Rahat and Shapira (2017), the study compares fifteen parliamentary radical left parties (RLPs) from eleven European countries – Cyprus, Czech Republic, Denmark, France, Finland, Germany, Greece, the Netherlands, Norway, Portugal and Spain – across the dimensions of participation, representation, competition, responsiveness and transparency. Specifically, the study outlines patterns across the IPD dimensions and investigates the extent of variation within the party family, juxtaposing it against ideological and structural distinctions among RLPs.